The impact of interpretation biases on psychological responses to the COVID-19 pandemic: a prospective study - Chan, Frederick H. F. (2022)
Background. This study investigates the longitudinal role of interpretation biases in the development and maintenance of health anxiety during the pandemic. Individual differences in behavioural responses to the virus outbreak and decision making were also examined. Methods. Two hundred seventy-nine individuals from a pre-pandemic study of interpretation bias and health anxiety completed an online survey during the third wave of the COVID-19 pandemic in Hong Kong. Participants’ health anxiety, interpretation biases, and COVID-specific behaviours (i.e. practice of social distancing, adherence to preventive measures, information seeking), and health decision-making were assessed. Results. Pre-pandemic tendencies to interpret ambiguous physical sensations as signals for illness did not predict health anxiety during the pandemic, b=−0.020, SE=0.024, t=−0.843, p=.400, 99% CI [−0.082, 0.042], but were associated with a preference for risky treatment option for COVID-19, b=0.026, SE=0.010, Wald=2.614, p=.009, OR=1.026, 99% CI [1.001, 1.054]. Interpretation biases and health anxiety symptoms during the pandemic were associated with each other and were both found to be significant predictors of practice of social distancing, adherence to preventive measures, and information seeking behaviour. Conclusions. This study adds to the growing evidence of the role of interpretation biases in health anxiety and the way that people respond to the ongoing pandemic.